"I wanted to be close to Roma." An interview with Nela Nezábudková - Gáborová-Kroková, Jana (Romano džaniben, 2022)
Interview with Nadežda Malčeková, who wrote two autobiographical books under the pseudonym Nela Nezábudková - Girl from the Monastery (2020) and Ďatelinka (2021). In the interview, she talks about her faith and life in a monastery, working at school, and the education of Romani children, but also about her childhood and the relationship with her parents. The interview is published in Slovak language.